2021
DOI: 10.3390/catal11101197
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrogen Electrosynthesis at Enhanced Current Density Using a Redox Polymer

Abstract: High-temperature tolerant enzymes offer multiple advantages over enzymes from mesophilic organisms for the industrial production of sustainable chemicals due to high specific activities and stabilities towards fluctuations in pH, heat, and organic solvents. The production of molecular hydrogen (H2) is of particular interest because of the multiple uses of hydrogen in energy and chemicals applications, and the ability of hydrogenase enzymes to reduce protons to H2 at a cathode. We examined the activity of Hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…Apparently, CO-binding to the H-cluster did not result in an irreversible damage of the oxidation state (Hred) of the H-cluster, which was shown in other CO inhibition studies for [FeFe]-hydrogenases before (Goldet et al, 2009;Baffert et al, 2011;Foster et al, 2012). Noteworthy, the HDCR from T. kivui also showed a substantial reversibility of CO-dependent inactivation in enzymatic electrosynthesis experiments (Ruth et al, 2021).…”
Section: Discussionsupporting
confidence: 52%
“…Apparently, CO-binding to the H-cluster did not result in an irreversible damage of the oxidation state (Hred) of the H-cluster, which was shown in other CO inhibition studies for [FeFe]-hydrogenases before (Goldet et al, 2009;Baffert et al, 2011;Foster et al, 2012). Noteworthy, the HDCR from T. kivui also showed a substantial reversibility of CO-dependent inactivation in enzymatic electrosynthesis experiments (Ruth et al, 2021).…”
Section: Discussionsupporting
confidence: 52%
“…S4). Indeed, the enzyme was inhibited by CO and 50% inhibition was observed with 204.7 ± 5.3 μM CO, indicating a high tolerance for CO in vitro, compared with other hydrogenases (13,16,42). Last, we assessed the impact of ions on the Fd 2-:H + oxidoreductase activity.…”
Section: Basic Biochemical Properties Of Ech2mentioning
confidence: 98%
“…59 In the field of hydrogen production, numerous enzyme-electroreduction systems were investigated for their potential to deliver improvement in energy efficiency. [60][61][62] Hardt et al 63 reported an example of such enzymatic systems (hydrogenase embedded in a hydrogel), allowing production of hydrogen with only 12 mV overpotential.…”
Section: Pathways To Energy Input Reduction: Hydrogenmentioning
confidence: 99%